Kristologi dalam Kehidupan Sehari-Hari dan Relevansi Ajaran Kristus Bagi Umat Kristen - Juliana Waruwu; Rencan Carisma Marbun (Pusat Riset dan Inovasi Nasional, 2025)
One branch of Christian theology is Christology which focuses on the study of Jesus Christ. Specifically, it talks about who Jesus Christ is, His nature as God and man (Divine nature and human nature), His position, His presence as a savior, reconciler, redeemer of human sins and talks about the teachings of Christ that are useful in everyday life for Christians. Studying Christology, increases knowledge and also knows His teachings that function to help face life's challenges. Christology is not just a religious study but is useful for strengthening faith, increasing hope, and improving the spiritual life of Christians. This research was conducted using a qualitative approach through literature study. This research concluded that by studying Christology and the teachings of Christ, as Christians we can emulate what Christ taught such as love and forgiveness, sacrifice and service and behavior in life.